THE EFFECTIVENESS OF TEACHING LISTENING WITH A BLENDED-BASED CANVAS MODEL AT THE UNIVERSITY LEVEL - Wahyuni, Erly -; Soeparto, Soeparto (Premise: Journal of English Education and Applied Linguistics, 2023)
The research is to know whether the blended-based canvas model is effective or not used in Listening classes. An experimental design was applied with a  mixed method. The quantitative design used was a pretest-posttest experimental and control group design to examine if such a model of learning can affect their comprehension of Listening and a qualitative one to know their responsibilities towards the model. Two classes of third-semester students are selected randomly as research subjects, and each group consists of 32 students. The pretest-posttest scores are analyzed using a t-test. The result of the t-test indicates if there is an increase in the pre-test results after giving treatment (post-test), with the final score being 93.05 for the experimental class and 84.58 for the control class. It reveals that the listening activities designed with blended-based learning in the experiment class are practical. The student's response to this listening model is positive even though the online platform model still has weaknesses. The students can access their courses anywhere and anytime, with no time limitation and dynamic interaction between the teachers and students, and they can also get e-materials quickly.